Respuesta :
2 = -3x + 26
First, subtract '26' from both sides.
[tex]2 - 26 = -3x[/tex]
Second, subtract '2 - 26' to get '-24'.
[tex]-24 = -3x[/tex]
Third, divide both sides by '-3'.
[tex] \frac{-24}{-3} =x[/tex]
Fourth, change the fraction into a negative.
[tex] \frac{24}{3} =x[/tex]
Fifth, since 3 × 8 = 24, simplify the fraction to '8'.
[tex]8 = x[/tex]
Sixth, switch it around.
[tex]x = 8[/tex]
Answer: x = 8
First, subtract '26' from both sides.
[tex]2 - 26 = -3x[/tex]
Second, subtract '2 - 26' to get '-24'.
[tex]-24 = -3x[/tex]
Third, divide both sides by '-3'.
[tex] \frac{-24}{-3} =x[/tex]
Fourth, change the fraction into a negative.
[tex] \frac{24}{3} =x[/tex]
Fifth, since 3 × 8 = 24, simplify the fraction to '8'.
[tex]8 = x[/tex]
Sixth, switch it around.
[tex]x = 8[/tex]
Answer: x = 8
X=8 because you would do -26 under the postive 26 and they would cancel then do the same to the other side and you would get -24=-3x and put the -3x over -3,they would cancel then you do the same to the other side and you would get X=8! Hope this helped!